Arquitectura e Transcendência; Um projecto para o Caminho de Santiago - Hugo Miguel Valente Gomes (2018)
Reflection and self-analysis of the in loco experience of the realization of one of the ways to Santiago, in which its conclusion results in the creation of a new concept, a new spatial, social and cultural experience through the reinterpretation of concepts, function and implicit functioning of the places where I spent the night, with the intention of projecting a different place in the course. The purpose is to captivate and create impact in those who live in it. To return to origins, to the vernacular, to show the value of simple things and thereby to make the banal becomes something transcendental. I think that everything that surprises us, that has an impact on the innermost part of our being, which creates a rupture in our everyday life experiences, originates in the background a shrewder interaction of the senses and transforms us considering that everything depends on multiple factors being the state of consciousness of each individual the focal point to achieve this end. The goal is to create, through an architectural construction, subtle stimuli in order to provoke a "sensitized conscience" in the user. Design a building where the small peculiarity and details, whether constructive or spatial, provide the ability to connect with the essence of the transcendental. Citing the maxim attributed to Mies Van Der Rohe, "God is in the details". Therefore, transcendence can be a matter of seeing and feeling.